Design of a low voltage 0.18 um CMOS Surface Acoustic Wave gas sensor - Moghavvemi, M.; Attaran, A. (IFSA, 2011)
A Surface Acoustic Wave (SAW) gas sensor is designed and tested in this paper. The objective of the designed SAW Gas sensor is to detect H2S and NOX gases. The inter-digital transducers (IDT) antennas in the proposed sensor are coated with thin film WO3, which mass is sensitive to mentioned gas concentrations upon close contact. The changes in WO3 mass are registered as frequency shift from 300 to 500 MHz. The sensor blocks are simulated, fabricated and tested for an operating frequency of 300 MHz to 350 MHz. A relatively linear response is achieved with a step of 0.1 V for 10 MHz step frequency shift emitted from WO3 coated IDTs. This fully integrated signal processing circuitry designed by 0.18 um CMOS process is simple, cost effective, small in size, has low power consumption, and fast real-time operation response as well.